Climate-smart agriculture investment portfolios in Guyana: a way forward - Navarrete Frías, Carolina; Lizarazo, Miguel; Eitzinger, Anton; Mwongera, Caroline; Sandoval, Danny; Rosales, Judith; Bullen, Pauline; Daggers, Louisa; Benn, Dina; Nanlall, Satesh (2021)
Guyana has densely populated coastal regions and relatively inaccessible Hinterland and is highly vulnerable to climate change and climate variability. The agriculture sector requires a transformation towards climate-resilient agriculture systems. In order to respond to this priority, the Alliance of Bioversity International and CIAT, the Ministry of Agriculture of the Government of Guyana and local partners, joined efforts to develop and implement a Caribbean Development Bank (CDB) financed project, ‘Development of a Framework for Prioritizing Climate-Smart Agriculture (CSA)’. Interventions were focused on two regions in Guyana - Region 3 (Essequibo Islands-West Demerara) and Region 9 (Upper Takutu-Upper Essequibo).